National business cultures: the influence of religion, and their role in the economic development of countries - Chebotarov, Viacheslav; Chebotarov, Iegor (Bulletin of Geography. Socio-economic Series, 2020)
The paper clarifies the conditions and factors of the development of the institutional environment through modern interdisciplinary analysis. The authors revise the studies of the problem under consideration in the history of science and reveal the decisive role of religion in the development of national business cultures. The study highlights the fundamental postulates, i.e. the canons of theology, and argues for the need to consider them in the context of the analysis of national business cultures. The authors put forward and prove theoretical and methodological principles of the determinant influence of national business cultures and religion on the development of countries (the socio-economic phenomenon of the “economic miracle”). The content of the category “Polish economic miracle” is revealed through analysis of the influence of Catholicism, Orthodoxy and Protestantism on other “economic miracles” known from history. The authors conclude that Catholicism currently encourages entrepreneurial initiative of both individuals and organisations, which contributes to the sustainable economic development of countries.